Circulating tumour DNA reflects treatment response and clonal evolution in chronic lymphocytic leukaemia - Paul Yeh (Nature Communications, 2017)
Disease monitoring of chronic lymphocytic leukaemia (CLL) is a challenge. Here, the authors show that serial ctDNA analysis in 32 CLL patients allows monitoring of clonal dynamics over time, and identifies the emergence of genomic changes associated with Richter’s syndrome.